G0 Potato Seed Production Management in Indonesia: An Overview and The Challenges - Asma Sembiring; Rini Roro Murtiningsih; Kusmana Kusmana (AGRARIS: Journal of Agribusiness and Rural Development Research, 2021)
The availability of Indonesian potato seed and production of potato for consumption depends on the availability and quality of Generation 0 (G0) potato seed. This study aims to observe G0 potato seed production management in Indonesia. Data were collected through Focus Group Discussion (FGD) and survey. Thirty-seven G0 potato seed producers participated in the survey. Data were analyzed descriptively, while the feasibility of the farm budget of G0 potato production was calculated using the enterprise budget method. The results showed that the producers had challenges on capital to broaden the screen house to extend the production scale and limited plantlet availability. Meanwhile, they did not have any problems with other production aspects, such as controlling pests and diseases and the marketing of the G0 seed. Government supports to provide screen houses to fulfil producers' necessity and delegate the legality of potato plantlets are needed to create a better Indonesia's potato seed system.